Pengelolaan Harta Wakaf: Studi Komparasi Nahdlatul Ulama dan Muhammadiyah Kabupaten Banyuwangi - Ansari Ansari (Program Pascasarjana Universitas Ibrahimy, 2019)
Waqf specifically can help activities in society. However, the management of waqf of Nahdlatul Ulama and Muhammadiyah in Banyuwangi Regency is not professional because Nadzir's human resources are low. This research is a descriptive qualitative using a sociological empirical approach. The results of this research show that first, the waqf management of Nahdlatul Ulama and Muhammadiyah has categorized into Mahdhah worship (main worship), which is most of the waqf material is intended for physical development. Second, the problems of waqf management are the control system weakness and the lack of understanding and awareness of the society towards waqf. Third, efforts in waqf management must be carried out by an integrated and well-planned arrangement. Those include human resource development of Nadzhir, implementation of control and supervision system so that waqf can be managed optimally and beneficial for social interests.